Evaluation of excess skin in Swedish adults 18–59 years of age. Issue 2 (4th March 2017) - Ockell, Jonas; Elander, Anna; Staalesen, Trude; Olsén, Monika Fagevik
Abstract: Background: Little is known about excess skin in the normal population. The aim of this study was, therefore, to analyse the prevalence, impairments, and discomfort of excess skin in a cross-section of the Swedish population. Methods: From the population registry of the Swedish Tax Agency, 1408 subjects living in Västra Götaland County from 18–59 years of age were randomly selected with an equal distribution of the sexes. Additionally, age was equally distributed, although twice as many subjects under 40 years of age were sent the questionnaire due to an expected low response rate for younger people. All subjects were asked to fill out the Sahlgrenska Excess Skin Questionnaire (SESQ), which included questions concerning the amount of and discomfort due to excess skin. Results: No excess skin was reported by 78% of responders, including 71% of women and 87% of men. The responders who reported any excess skin were significantly older, had a higher body mass index (BMI) and reported larger differences between their maximum and current BMI. The most common reported site of excess skin was the abdomen in both women and men (26% and 8%, respectively), and this was reported to cause the most discomfort (median 4 and 2, respectively, on a scale from 0–10). Women graded psychosocial symptoms significantly higher than men, but there were no significant differences in other symptoms. Conclusions: The results indicate that Swedish adults, regardless of sex, do not suffer from excess skin and may be considered as reference values.